Pengaruh Kualitas Kehidupan Kerja (Quality Of Work Life), Budaya Organisasi Dan Gaya Kepemimpinan Terhadap Komitmen Organisasional (Studi Pada Dinas Pekerjaan Umum Dan Penataan Ruang Kota Malang) - Ahmad Dicky Husnan; Muhammad Mansur; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThis research was conducted at the Department of public works and spatial planning in Malang City. The type of research used is explanatory research (quantitative research) through a quantitative approach. The purpose of this study was to determine the effect of work life quality, organizational culture, and leadership style on organizational commitment. The independent variable used is the quality of work life, organizational culture, and leadership style, while the dependent variable is organizational commitment. The sample used in this study were 52 respondents who were members of the civil service (PNS) employee. Data collection techniques using a questionnaire. The analytical methods used are instrument test, morality test, multiple linear regression analysis, classic assumption test, determination test, f test and t test using the help of computer software SPSS 25 data processing. The results of this study indicate that the quality of work life has a positive and significant effect on organizational commitment, organizational culture has a positive and significant effect on organizational commitment, leadership style influences organizational commitment.Keywords: Organizational commitment, Quality of Work Life, Organizational Culture, Leadership Styles.